Radial dependence of thermal transport in silicon nanowires. (27th November 2018) - Verdier, Maxime; Han, Yang; Lacroix, David; Chapuis, Pierre-Olivier; Termentzidis, Konstantinos
Abstract: A radial decomposition of the heat flux in a silicon crystalline nanowire is studied with molecular dynamics (MD) and Monte Carlo (MC) simulations. Less heat flux is carried in the external layer of nanowires than in the center. The difference between the center and the surface is of the order of 50% and 30% with MD and MC simulations, respectively. As a result, a heat flux close to the surface is 30% and 15% lower than the total axial heat flux in the structure. The physical mechanism behind is analyzed from partial contribution of each atom in each phonon mode calculated from lattice dynamics. The reduction of the flux close to the surface is related to back-scattering, the amorphous-like DOS of the external layer and flattened dispersion curves, thus lower phonon group velocities. Our study points to the need for cautions analysis of experimental determination of the thermal conductivity involving contact measurements, such as scanning thermal microscopy.